ANALISIS PERPUTARAN PIUTANG TERHADAP LIKUIDITAS - POPON RABIA ADAWIA; AYU AZIZAH; YULI SETYARINI (Jurnal Akademika, 2019)
This study examines the factors that influence the liquidity of PT. Indofood CBP Sukses Makmur Tbk. Referring to two variables, namely turnover as a dependent variable / dependent variable (x) and liquidity as independent variable / independent variable (y). The purpose of this study was conducted is to determine whether or not a positive and significant influence between receivables turnover and the level of corporate liquidity. And to know how big influence of receivable turnover to the level of corporate liquidity. The research method used in conducting this research is the research method of associative description. This test is performed by using the collation test used to test whether there is a relationship or not between receivables turnover to corporate liquidity. The results obtained from testing the hypothesis of collation and simple regression is there is a significant relationship between receivables turn over to liquidity. For the regression equation from time series 2010 to 2016 can be determined in equation Y = 248.097 + 0.56X. This research yields conclusion that receivable turn over influence to level of liquidity of PT. Indofood CBP Sukses Makmur Tbk. This result can be seen from tcount of 0.55 The effect of receivable turnover variable to the level of liquidity of 5.80% while the rest of 94.91% influenced by other variables outside this study.Keywords: Accounts receivable, liquidity, Financial Statement, Balance Sheet.